Synthesis, Antimicrobial Study, and Molecular Docking Simulation of 3,4-Dimethoxy-β-Nitrostyrene Derivatives as Candidate PTP1B Inhibitor - Salman Alfarisi; Mardi Santoso; Alfinda Novi Kristanti; Imam Siswanto; Ni Nyoman Tri Puspaningsih (MDPI AG, 2020)
A derivative series of 3,4-dimethoxy-β-nitrostyrene was synthesized through nitroaldol reaction, including a new compound of 3,4-ethylenedioxy-β-bromo-β-nitrostyrene. The antimicrobial activity effect of 3,4-alkyloxy modification of β-nitrostyrene was investigated. A molecular docking study was also performed to obtain information about their interactions with protein tyrosine phosphatase 1B (PTP1B). The active residues of cysteine-215 and arginine-221 of PTP1B play a key role in signaling pathways that regulate various microorganism cell functions. It also acts as a negative regulator in signaling pathways of insulin that are involved in type 2 diabetes and other metabolic diseases. These derivatives exhibited potential antifungal activity. The studied compounds were also had potential as fragments to be PTP1B inhibitors by interacting with serine-216 and arginine-221 residues, according to their molecular docking. 3,4-Ethylenedioxy-β-methyl-β-nitrostyrene was the most successful potential candidate as a PTP1B inhibitor. However, further research is needed to investigate their potential for medicinal use.